Mode of Delivery of Women with Complicated Pregnancy in a Tertiary Level Hospital in Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Every year, a great number of women die from pregnancy or childbirth related complications, which can be prevented. In developing countries, they don’t have access to maternal health services and cannot afford high quality care. Maternal death is usually occurs due to three delays: in decision making to seek care, reaching care and receiving care. Right decision at the right time regarding mode of delivery has a direct impact on healthy outcome of pregnancy as well as the maternal wellbeing.Objectives: To find out the outcome of complicated pregnancy.Materials and Methods: This cross-sectional observational study was conducted at obstetrics and gynaecology department of Dhaka Medical College Hospital from January to June 2011. Total 107 mothers who delivered recently with or without pregnancy complications were selected purposively. Data were collected by face to face interview with semi structured questionnaires. Verbal consents were taken prior to interview.Results: Among the respondents about 68.2% had antenatal complications and about 31.8% had no antenatal complication. Among the women having antenatal complications, 83.6% delivered by caesarean section and only 16.4% delivered by normal vaginal delivery. There was significant association of antenatal complications with mode of delivery by caesarean section.Conclusion: Women having antenatal complications had significant association with caesarean section. Though every pregnancy is at risk but early detection of complications, timely referral and timely intervention can save lives of many women during the process of child birth.JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 31-34